Indigenous Innovation
VIII, 214 p.
Keywords: Rooted in diverse cultures and in distinct regions of the world, Indigenous people have for generations created, maintained, and negotiated clear and explicit relationships with their environments. Despite numerous historical disruptions and steady iterations of imperialism that continue through today, Indigenous communities embody communities of struggle/resistance and intense vitality/creativity. In this work, a fellowship of Indigenous research has emerged, and our collective intent is to share critical narratives that link together Indigenous worldviews, culturally-based notions of ecology, and educational practices in places and times where human relationships with the world that are restorative, transformative, and just are being sought.